Internal Audit in Territorial Self-Government Units in Light of Forthcoming Changes - Kołodziej, Dominika (Audyt wewnętrzny w jst w świetle nadchodzących zmian, 2022)
The purpose of this article was a description and justification of the direction of changes which inevitably await the area of the functioning of the internal audit within the territorial self- -government units in Poland. The analysis was preceded by a review of the evolution of the functioning and the definition of the internal audit within the territorial self-government units in Poland over the last twenty years. The sources and causes of the planned legislative changes in the act on public finance concerning the internal audit in the sector of public finance in Poland are presented with a special emphasis on the territorial self-government units. The conducted research is based on the study of literature on public finance, internal audit, and managerial control. A detailed analysis and interpretation of legal acts in force in the researched area was conducted, particularly including the draft bill amending the public finance act and certain other acts (no UD327 in the list of legislative and programme works of the Council of Ministers as of 1st March 2022) to justify the direction of the changes.
Financial Sciences. Nauki o Finansach, 2022, vol. 27, no. 2, s. 1-11
Keywords: managerial control; functioning of the internal audit; territorial self-government units; administration efficacy of the territorial self-government units; kontrola zarządcza; funkcjonowanie audytu wewnętrznego; jednostki samorządu terytorialnego; efektywność gospodarowania jednostkami samorządu terytorialnego